OneWorldGiving : Uniting NGO’s and Donors for a Better World - Pandey, Shreya; Afaq Shaikh; Siddhi Keni; Uma Garodiya; Ayush Yadav (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
"OneWorldGiving: Uniting NGOs and donors for a Better World" is a project aiming to bridge the gap between donors and NGOs in India’s philanthropic scene. The initiative aims to create a platform that promotes efficiency, transparency, and cooperation, fostering shared responsibility and trust among all parties involved. Other studies have focused on cloud-based mobile applications, automation of donation procedures using Azure Logic Apps, Android app for receiving food, clothing, and book contributions, and mobile applications for community projects and NGOs. However, challenges such as platform-specific specifications, outdated devices, and specialist knowledge in Flutter programming may arise. The NGO Portal website aims to help NGOs and potential volunteers interact, promoting a sense of community and unity among stakeholders. The Android application focuses on making book contributions to NGOs easier, with a Donation Registration component, Firebase database, and User Management feature. The project aims to create a transformative platform that promotes cooperation, openness, and group compassion, improving lives for those in need.